An Empirical Study on Demographic Correlates of Emotional Intelligence of Engineering Students - Rama Devi, V.; Lakshmi Narayanamma, P. (Prabandhan: Indian Journal of Management, 2015)
The study aimed to explore the relationship between demographic factors and emotional intelligence of engineering students. The survey was conducted among 177 engineering students with the help of a structured questionnaire. The data collection instrument was tested for reliability, and Cronbach’s alpha was found to be 0.752, thereby ensuring the reliability of the instrument. The data was analyzed using various statistical tools like t - test, mean, standard deviation, ANOVA, and chi-square test. The findings revealed that gender significantly influenced emotional intelligence, but schooling and background of the students did not exert a significant impact. The results also showed that emotional intelligence is independent of age, father’s education and occupation, mother’s education, family size, and income, but not mother’s occupation.